Digital Pedagogical Model Based on Climate Change Issues Integrated with Virtual Reality Technology to Enhance Students' Critical Thinking and Climate Change Awareness - Suryati, Suryati; Pangga, Dwi; Habibi, Habibi; Azmi, Irham (Faculty of Engineering and Applied Science, 2025)
Climate change education is crucial for equipping students to tackle pressing global challenges, yet traditional methods often fail to foster critical thinking (CT) and awareness. This study aimed to develop a digital pedagogical model based on climate change issues integrated with Virtual Reality (VR) technology to enhance students' CT and climate change awareness. The research employed a Research and Development (R&D) approach, involving validation, practicality testing, and effectiveness evaluation. Validity data were obtained through expert validation (involving five validators), while practicality and effectiveness data were gathered through implementation processes involving two observers (evaluating model practicality) and 38 high school students (effectiveness test subjects). Implementation utilized a pretest-posttest design and was analyzed descriptively and quantitatively. The findings indicate that the model is valid, with an average validation score of 4.15, and practical, with an implementation score of 4.80 categorized as